Influence of pregnant couples' attitudes towards sex during pregnancy on sexual function - Moon Jeong Kim (Korean Journal of Women Health Nursing, 2020)
Purpose This study was conducted to identify the influences of the attitudes of pregnant women and their husbands towards sex during pregnancy on sexual function. Additional purpose was to compare the frequency of sexual dysfunction according to gender and gestational trimester and to describe the changes in sexual behavior according to the gestational trimester. Methods In this study, 231 pregnant couples completed self-report questionnaires during their visits to women’s hospitals or community health centers. The questionnaires assessed general characteristics, maternal/paternal sexual attitudes towards sex during pregnancy (Maternal Sex during Pregnancy Scale, MSP/Paternal Sex during Pregnancy Scale, PSP), and sexual function (using the Female Sexual Function Index and International Index of Erectile Function, respectively). Multiple regression analysis was done to test the research model using SPSS version 23.0. Results In this study, 74.9% of pregnant women and 38.5% of their husbands reported sexual dysfunction. Sexual dysfunction was prevalent in pregnant women in the first trimester and prevalent in husbands in the third trimester. MSP (β=.44, p<.001) in pregnant women and PSP (β=.39, p<.001) and being in the first trimester (β=.17, p=.012) in husbands influenced sexual function during pregnancy. In the first trimester, the scores for attitudes towards sex during pregnancy were the lowest in pregnant women, while they were the highest in their husbands. Conclusion Positive attitudes about sex during pregnancy are important for sexual function in pregnant couples. Because the difference in attitudes towards sex during pregnancy between pregnant women and their husbands was greatest in the first trimester, sexual health interventions need to be provided in early pregnancy.